Chemical Evolution of a Bacterial Proteome1. Issue 34 (1st July 2015) - Hoesl, Michael Georg; Oehm, Stefan; Durkin, Patrick; Darmon, Elise; Peil, Lauri; Aerni, Hans‐Rudolf; Rappsilber, Juri; Rinehart, Jesse; Leach, David; Söll, Dieter; Budisa, Nediljko
Abstract We have changed the amino acid set of the genetic code of Escherichia coli by evolving cultures capable of growing on the synthetic noncanonical amino acid L‐β‐(thieno[3, 2‐b]pyrrolyl)alanine ([3, 2]Tpa) as a sole surrogate for the canonical amino acid L‐tryptophan (Trp). A long‐term cultivation experiment in defined synthetic media resulted in the evolution of cells capable of surviving Trp→[3, 2]Tpa substitutions in their proteomes in response to the 20 899 TGG codons of the E. coli W3110 genome. These evolved bacteria with new‐to‐nature amino acid composition showed robust growth in the complete absence of Trp. Our experimental results illustrate an approach for the evolution of synthetic cells with alternative biochemical building blocks.